Management of Zakat, Infaq, and Shodaqoh Funds on MSME Empowerment Program in Lazismu West Kalimantan - Rahmat, Rahmat; Anwari, M. Khairul; Primayudia, Doddy; Supriadi, Fenni (Tujjar International Journal of Islamic Economics Development, 2023)
This study aims to determine the management procedures for ZIS (zakat, infaq, and shodaqoh) in the MSME empowerment program organized by Lazismu. This research method uses a qualitative descriptive research method approach, namely data collection techniques including observation, interviews and documentation in obtaining information related to the management of ZIS fund. The results showed that in the distribution of ZIS funds in the empowerment of MSMEs, it is expected to improve the economy of the people by carrying out MSME empowerment program activities that have been planned by Lazismu. There are two patterns of approach that can be chosen by prospective mustahik, including the empowerment of bound and unbound MSMEs. First, the empowerment of bound MSMEs is the empowerment of MSMEs that has been provided by Lazismu Kalbar (West Kalimantan) which is intended for mustahik. Second. The empowerment of unbound MSMEs is an empowerment intended for mustahik who apply for assistance to MSMEs that are just about to be run or that have been run by mustahik